A Field Experiment in Motivating Employee Ideas - Susanne Neckermann; Michael Gibbs; Christoph Siemroth (Tinbergen Institute, 2014)
We study the effects of a field experiment designed to motivate employee ideas, at a large technology company. Employees were encouraged to submit ideas on process and product improvements via an online system. In the experiment, the company randomized 19 account teams into treatment and control groups. Employees in treatment teams received rewards if their ideas were approved. Nothing changed for employees in control teams. Our main finding is that rewards substantially increased the quality of ideas submitted. Further, rewards increased participation in the suggestion system, but decreased the number of ideas per participating employee, with zero net effect on the total quantity of ideas. The broader participation base persisted even after the reward was discontinued, suggesting habituation. We find no evidence for motivational crowding out. Our findings suggest that rewards can improve innovation and creativity, and that there may be a tradeoff between the quantity and quality of ideas.
Keywords: C93; J24; M52; O32; 330; innovation; rewards; creativity; field experiment